Star Wars : the complete visual dictionary - Luceno, James, 1947-; Reynolds, David West; Windham, Ryder; Ivanov, Alexander (New York : DK Publishing, 2018)
Contains illustrated descriptions of people, creatures, places, weapons, and other aspects of the Star Wars saga.
Material in this book was originally published in various DK publications in 1998 through 2018.
Includes index.
All Grades.
Keywords: Star Wars films -- Miscellanea -- Juvenile literature; Star Wars films -- Miscellanea; Star Wars films -- Juvenile literature; Star Wars films -- Pictorial works -- Juvenile literature